Factors Affecting the Metabolic Conversion of Ciprofloxacin and Exposure to Its Main Active Metabolites in Critically Ill Patients: Population Pharmacokinetic Analysis of Desethylene Ciprofloxacin - Martin Šíma; Daniel Bobek; Petra Cihlářová; Pavel Ryšánek; Jaroslava Roušarová; Jan Beroušek; Martin Kuchař; Tomáš Vymazal; Ondřej Slanař (MDPI AG, 2022)
The objective of this prospective study was to examine the exposure to the main active metabolites of ciprofloxacin in critically ill patients and to examine the factors (demographic, laboratory and genetic) that could potentially affect the drug metabolic conversion of ciprofloxacin. The secondary aim was to develop a population pharmacokinetic model for the metabolite showing the most associations with the abovementioned factors. A total of 29 patients were treated with intravenous infusion of ciprofloxacin and enrolled on this trial. Blood samples for pharmacokinetic analysis were taken at 1, 4, and 11.5 h following the completion of the infusion. Sex, age, body weight, height, serum creatinine and bilirubin levels, and creatinine clearance (CLCR) were recorded, and polymorphisms rs2032582 and rs1045642 in the ABCB1 gene, rs4148977 in the SLCO1A2 gene and rs762551 in the CYP1A2 gene were analyzed. A three-stage parent drug-metabolite population pharmacokinetic model was developed. Median (IQR) metabolite/parent ratios of the desethylene ciprofloxacin, formyl ciprofloxacin and oxociprofloxacin were 5.86 (4.09-9.87)%, 4.08 (3.38-6.92)% and 5.91 (3.42-13.65)%, respectively. The desethylene ciprofloxacin metabolic ratio was positively associated with height (r2 = 0.2277, p = 0.0089) and CLCR (r2 = 0.2023, p = 0.0144) and negatively associated with age (r2 = 0.2227, p = 0.0112). Males had a significantly higher oxociprofloxacin metabolic ratio than females (9.14 vs 3.42%, p = 0.0043). In the desethylene ciprofloxacin population PK model, the volume of distribution decreased with age, the parent drug-metabolite transfer rate constant increased with CLCR, and the metabolite elimination rate constant decreased with age and is increased in CYP1A2 rs762551 variant allele carriers. We therefore hypothesized that the CYP1A2 inhibition by ciprofloxacin is mediated by its metabolite desethylene ciprofloxacin.